Biological activities of two major copaiba diterpenoids and their semi-synthetic derivatives - Serhat Sezai Çiçek and Arlette Wenzel-Storjohann and Ulrich Girreser and Deniz Tasdemir (Revista Brasileira de farmacognosia, 2020)
The oleoresin of Copaifera reticulata Ducke, Fabaceae, is a traditional Brazilian remedy used for a wide range of applications. Commonly named copaiba, the oleoresin has been found to exhibit strong antimicrobial effects in our previous study, which could be attributed to some of its diterpenoid constituents. In order to find new biological activities and to eventually enhance the before observed effects, (−)-polyalthic acid (1) and kaurenoic acid (2), together with eight prepared semi-synthetic derivatives (1a–1c and 2a–2e) were evaluated for their cytotoxic, antibacterial and antifungal properties. Regarding the gram-positive bacteria Enterococcus faecium and methicillin-resistant Staphylococcus aureus, we found that both the exocylic methylene group and the carboxyl group were crucial for the activity against these two clinically relevant bacterial strains. Investigation of the antifungal activity, in contrast, showed that the carboxyl group is unnecessary for the effect against the dermatophytes Trichophyton rubrum and Cryptococcus neoformans, indicated by low micromolar IC50 values for both (−)-polyalthic acid diethylamide (1a) as well as (−)-polyalthic acid methyl ester (1b). Apart from studying the biological activity, the structure of one semi-synthetic derivative, compound 1c, is being reported for the first time. During the course of the structure elucidation of the new compound, we discovered inconsistencies regarding the stereochemistry of polyalthic acid and its stereoisomers, which we clarified in the present work. [Figure not available: see fulltext.]
Keywords: Diterpene acid; MRSA; Natural product; NMR; Partial synthesis; Traditional medicine